Catastrophic Antiphospholipid Syndrome: A Review - Carmine Siniscalchi; Manuela Basaglia; Michele Riva; Michele Meschi; Tiziana Meschi; Giampiero Castaldo; Pierpaolo Di Micco (Immuno, 2023)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by thrombotic or obstetric events occurring in individuals who have persistent antiphospholipid antibodies. Catastrophic antiphospholipid syndrome (CAPS) is a rare and potentially fatal form of APS characterized by severe thrombotic complications occurring in multiple organs over a short period of time or simultaneously. CAPS is associated with a high (50%) death rate. Infections, multi-organ failure, and cerebral and heart thrombosis represent the main complications of this syndrome. Generally, anticoagulants, glucocorticoids, therapeutic plasmapheresis (TPE), and intravenous immunoglobulin (IVIG) are used in combination for treatment. Multidisciplinary care involving different specialists from hematology, rheumatology, nephrology, infectious disease, critical care, and obstetrics is often required due to the complexity of the disease. Recent data emphasize the effectiveness of biologics such as anti-TNF-a monoclonal antibodies (adalimumab, certolizumab), anti-CD38 monoclonal antibody (daratumumab), BAFF/Blys inhibitor (belimumab), and BTK inhibitor (zanubrutinib) against CAPS. In order to understand the underlying causes of CAPS, one future possibility involves investigating and characterizing the hereditary and acquired risk factors associated with CAPS.